PREVENTION OF BONE MINERAL LOSS IN PATIENTS WITH INFLAMMATORY RHEUMATIC DISEASES - Irena Kafedjiska; Filip Guchev; Mimoza Nicolovska-Kotevska; Dubravka Antova; Emilija Sandevska; Maja Bojadjioska; Baskim Osmani; Slavica Shubeska Stratrova (Македонско лекарско друштво = Macedonian Medical Association, 2020)
Introduction. Corticosteroids are therapeutic support for many medical conditions including systemic inflammatory rheumatic diseases. Secondary osteoporosis is one of the major complications from this therapy. Bisphosphonates are indicated for prevention and treatment of corticosteroid-induced osteoporosis. Aim. In a retrospective cross-sectional study to assess the effect of the early use of bisphosphonates on bone mineral density in patients with inflammatory rheumatic diseases treated with corticosteroids. Methods. We compared bone mineral density in an examined group of 75 posmenopausal women with inflammatory rheumatic diseases on a corticosteroid therapy who were treated early with bisphosphonates, with a control group of 80 postmenopausal women with osteoarthritis who have never been treated with corticosteroids. Bone mineral density was measured at the lumbar spine and left femur using Dual X-Ray absorptimetry in both groups of subjects. Results. Patients with inflammatory rheumatic diseases had an average T-score at the lumbar spine of -2.19, and -1.41 at the left hip. The average T-score for the control group was -2.24 at the lumbar spine and -1.53 at the hip. Difference in T-score at the lumbar spine and the left hip between the two groups was 0.073 and 0.300 (P=0.639 and P=0.048), respectively. There was no statistically significant difference in the T-scores for both groups. Conclusion. Osteoporosis is more prevalent in patients with inlammatory rheumatic diseases, both at the hips and the spine. The early use of bisphosphonates in patients with inflammatory rheumatic diseases, especially in those who are on corticosteroids, can prevent the loss of bone mineral density
ПРЕВЕНЦИЈА НА ГУБИТОК НА МИНЕРАЛНА КОСКЕНА ГУСТИНА КАЈ ПАЦИЕНТИ СО ИНФЛАМАТОРНИ РЕВМАТСКИ БОЛЕСТИ
Keywords: inflammatory rheumatic diseases; osteoarthritis; corticosteroids; osteoporosis; bisposphonates